Trading regularity and fund performance - BUSSE, Jeffrey (Institutional Knowledge at Singapore Management University, 2019)
We construct a new measure of trading regularity, capturing the extent to which investors trade on a regular basis. Institutional investors that regularly trade outperform those that trade less regularly. The performance of funds that regularly trade persists for at least a year. Among those who trade most regularly, larger funds perform relatively worse, because they incur higher transaction costs associated with their larger trades. Institutions that regularly trade generate superior performance, in part, by behaving as contrarians and by trading more aggressively on information. By contrast, we find no relation between trading regularity and performance among index funds.